Forensic Age Estimation from Proximal End of Femur: A Radiological Study in Living Individuals - Ninad Nagrale1, Swapnil Patond2, Ranjit Ambad3, Nandkishor Bankar4, Karan Jain5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Age determination is a very essential work in the field of forensic anthropology, which is a scientific studyof human skeleton to determine age, sex and time of death to identify an individual. The identification isnothing but the recognition of an individual through various physical features or biological parameters.This study aims to examine the relationship between the stage of epiphyseal union of ossification centres atproximal end of femur & biological age in Chhattisgarh population. The study was carried out in 140 healthysubjects (70 girls and 70 boys) aging from 13 to 20 years. The obtained results revealed that the completefusion of epiphysis of proximal end of femur is seen at 17-19 years. Females were consistently developingepiphysealunion at a younger age than their male counterparts with one year of difference. Results alsosuggest that the age of epiphyseal fusion at proximal end of femur is found to vary greatly all over the India,indicating the need for separate standards for separate regions.